The antioxidant behaviour of melatonin and structural analogues during lipid peroxidation depends not only on their functional groups but also on the assay system - Fagali, Natalia Soledad (2012)
There is no general agreement yet on the antioxidant effect of pineal indoles against lipid peroxidation. Accordingly, the main goal of the present work was to study the antioxidant activity of melatonin (MLT), N-acetylserotonin (NAS), 5-HO-tryptophan (5HO-TRP) and 5-methoxytryptamine (5MTP) in two different lipid systems with high content of polyunsaturated fatty acids (PUFAs): triglycerides (rich in 20:5 n-3, 22:6 n-3) dissolved in chloroform and sonicated liposomes made of retinal lipids (rich in 22:6 n-3). In the triglyceride-chloroform-system the peroxidation reaction was initiated by cumene hydroperoxide (CHP) whereas liposomes were peroxidized with Fe. 2+. The techniques employed at the present work were: (1) TBARS production, (2) DPPH assay, (3) determination of conjugated dienes production and (4) analysis of fatty acid profile by GC-MS. Butylated hydroxytoluene (BHT) was employed as a reference because of its well known antioxidant capacity. Our results showed that MLT and 5MTP were unable to protect PUFAs against lipid peroxidation in both systems, whereas NAS and 5HO-TRP were better antioxidants that BHT in the triglyceride-system but ineffective in the liposome-system. We conclude that the antioxidant behaviour of pineal indoles depends not only on their functional groups but also on the assay system and could be explained by the polar paradox theory.